2019
DOI: 10.20867/tosee.05.29
|View full text |Cite
|
Sign up to set email alerts
|

Branding Traditional and Natural Products by Providing Tourist Experience: What Are the Effects

Abstract: The mission of this research is to analyze how small producers of natural and traditional products can strengthen their position in the market and bring positive change to themselves and their stakeholders by establishing a brand and making it stronger through storytelling, organic certification and providing tourist experience. The study was approached inductively, by applying in-depth multiple source analysis on an identified exemplar case. The results show that creating a brand story and getting and present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…For example, a study on consumer behavior in Poland highlights statistically significant values for the "curiosity" criterion in food consumption as being very closely related to the tendency to consume these products, and the "recommend to a friend" criterion [55,[65][66][67][68]. In another study on the attitudes of young adult consumers (18-30 years) from seven European countries (Greece, Bulgaria, Romania, Slovenia, Croatia, Denmark the marquis of France) [69][70][71][72][73][74], it is reported that young people and adults from eastern European countries are more easily influenced by their friends and close relatives compared to those from western countries [31,56,[75][76][77][78][79][80]. The criteria "curiosity" (ST4) and "recommendation to a friend" (ST3) are statistically significant in the "residence" group (p < 0.05), with those who live in the urban environment being more open in all four selection criteria for traditional food products Additionally, the criterion "label" (ST7) (p = 0.010 < 0.05) is statistically significant for the socio-demographic characteristic "place of birth", where high values are attributed to respondents born in rural areas with rural origins.…”
Section: Results On Consumer Surveymentioning
confidence: 99%
“…For example, a study on consumer behavior in Poland highlights statistically significant values for the "curiosity" criterion in food consumption as being very closely related to the tendency to consume these products, and the "recommend to a friend" criterion [55,[65][66][67][68]. In another study on the attitudes of young adult consumers (18-30 years) from seven European countries (Greece, Bulgaria, Romania, Slovenia, Croatia, Denmark the marquis of France) [69][70][71][72][73][74], it is reported that young people and adults from eastern European countries are more easily influenced by their friends and close relatives compared to those from western countries [31,56,[75][76][77][78][79][80]. The criteria "curiosity" (ST4) and "recommendation to a friend" (ST3) are statistically significant in the "residence" group (p < 0.05), with those who live in the urban environment being more open in all four selection criteria for traditional food products Additionally, the criterion "label" (ST7) (p = 0.010 < 0.05) is statistically significant for the socio-demographic characteristic "place of birth", where high values are attributed to respondents born in rural areas with rural origins.…”
Section: Results On Consumer Surveymentioning
confidence: 99%